Assessing Marijuana Use, Anxiety, and Academic Performance Among College Students. Issue 2 (6th July 2019) - Wallis, Aaron L.; Gretz, David P.; Rings, Jeffrey A.; Eberle, Kiersten M.
Abstract : This article examines the relationship between marijuana use and anxiety symptoms among college students, with a secondary focus on marijuana use and grade point average (GPA). A secondary analysis was conducted on data obtained from the American College Health Association–National College Health Assessment. Results indicated that marijuana use was negatively associated with GPA among students with current anxiety and no formal treatment. The relationships between these variables may be more complex than previously thought.